2012
DOI: 10.1111/j.1365-2621.2012.03190.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antimicrobial activity of nisin in combination with allyl isothiocyanate against Listeria monocytogenes,Staphylococcus aureus,Salmonella Typhimurium and Shigella boydii

Abstract: Summary This study was designed to evaluate the synergistic antimicrobial effect of nisin and allyl isothiocyanate (AITC) against Listeria monocytogenes, Staphylococcus aureus, Salmonella Typhimurium and Shigella boydii. The synergistic interactions between nisin and AITC were observed against all foodborne pathogens, showing the fractional inhibitory concentrations <1. The populations of L. monocytogenes and S. aureus at the combined treatment of nisin and AITC were decreased to below 1 log CFU mL−1 after 10‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Similar results were obtained by Jin et al (2013) and Chen et al (2012) who found that chitosan coating containing 60 μl/ml AITC reduced Salmonella on egg shells and cantaloupe surfaces by 1.7 and N5.0 log 10 CFU/cm 2 , respectively, after 24 h at 22°C. The antimicrobial activity of AITC against foodborne pathogens is related to its ability to cause leakage of intracellular components (Lin et al, 2000;Zou et al, 2013), inhibit intracellular enzyme activity (Luciano and Holley, 2009) and disrupt cellular metabolism and energy production (Ahn, 2001;Chan et al, 2013).…”
Section: Viability Of C Jejuni On Chicken Breastsmentioning
confidence: 99%
“…Similar results were obtained by Jin et al (2013) and Chen et al (2012) who found that chitosan coating containing 60 μl/ml AITC reduced Salmonella on egg shells and cantaloupe surfaces by 1.7 and N5.0 log 10 CFU/cm 2 , respectively, after 24 h at 22°C. The antimicrobial activity of AITC against foodborne pathogens is related to its ability to cause leakage of intracellular components (Lin et al, 2000;Zou et al, 2013), inhibit intracellular enzyme activity (Luciano and Holley, 2009) and disrupt cellular metabolism and energy production (Ahn, 2001;Chan et al, 2013).…”
Section: Viability Of C Jejuni On Chicken Breastsmentioning
confidence: 99%
“…Although several studies reported that AITC was effective against various foodborne pathogens such as Escherichia coli O157:H7, L. monocytogenes, S. Typhimurium, Bacillus cereus, Staphylococcus aureus and Campylobacter jejuni, in vitro (Dufour et al, 2012;Lin, Kim, Du, & Wei, 2000;Shin, Harte, Ryser & Selke, 2010;Siahaan et al, 2013;Zou et al, 2013;Zou, Woo & Ahn, 2012) or in meat products including ground beef, fresh chicken, fermented sausage and Westphalian ham (Chacon, Muthukumarasamy, & Holley, 2006;Graumann & Holley, 2009;Luciano & Holley, 2009;Nadarajah, Han, & Holley, 2005), its high volatility, strong odor, poor water solubility and reactions with naturally occurring food nucleophiles limit its application in food systems (Chacon et al, 2006;Kim, Chung, Shin, Yam, & Chung, 2008). AITC is unstable in aqueous solution and is easily decomposed to new compounds, particularly under alkaline conditions or at elevated temperature (Ohta, Takatani, & Kawakishi, 1995;Tsao, Yu, Friesen, Potter, & Chiba, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AITC possesses also antimicrobial, antifungal, antioxidant, and anticarcinogenic properties (Zhang 2010;Minarini et al 2014). The antimicrobial activity of AITC was demonstrated on spoilage microorganisms, foodborne and postharvest pathogens, including gram-negative, gram-positive bacteria, and moulds (Lin et al 2000;Maria et al 2002;Rhee et al 2003;Wilson et al 2013;Zou et al 2013;Dias et al 2014). The antimicrobial activity of AITC is higher in the gas phase than in the liquid phase (Shin et al 2010).…”
mentioning
confidence: 99%